СИНТЕЗ ТА СПЕКТРАЛЬНІ ХАРАКТЕРИСТИКИ ПЕРСПЕКТИВНИХ НАНОРОЗМІРНИХ ВУГЛЕЦЕВИХ НОСІЇВ ДЛЯ АДСОРБЦІЙНИХ ТА КАТАЛІТИЧНИХ ПРОЦЕСІВ - Ogenko, Volodymyr; Orysyk, Svitlana; Kharkova, Ljudmila; Yanko, Oleg (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2020)
Processes of interaction between carbon quantum dots (CQDs) and solutions of rhodium, ruthenium and palladium chlorides in the surface layer have been investigated by electron and IR spectroscopy. When rhodium chloride is added to a solution of CQDS, a bathochromic shift of the β- and p-absorption bands (ABs) at 48725 and 41711 cm-1 as well as hypsochromic shift of the α-AB at 28935 cm-1 indicate that rhodium adsorption occurs on the surface of CQDs. The bathochromic shift of the absorption bands at 22400 сm1 together with the hypsochromic shift of ABs corresponding to d-d electron transitions in the metal ions indicates the formation of rhodium with CQDs. When ruthenium and palladium chlorides are added to an aqueous solution of CQDs, the intensive of ABs characterizing the complex anions [RuCl6]3-, [RuCl6]2- or [PdCl4]2- are absent in the UV-Vis spectra. This indicates the passage of adsorption processes of metals on the surface of CQDs. The present of ABs (at 27055 and 25125 сm-1) indicate the trivalent state of ruthenium ion; the p-ABs bathochromic shift as well as α-ABs hypsochromic shift indicates the probable complex formation of CQDs with Ru3+ ions. The change in the position of the absorption bands of d-d electron transitions (at 25448 сm1) together with the bathochromic shift of p-ABs and hypsochromic shift of α-ABs indicates a change in coordination environment in the palladium ion with the possible formation of Pd → N bond. The IR-spectra data of CQDs showed the presence of a number of characteristic ABs for functionalized CQDs: ν(N–H) at 3260 сm1, (C=O) at 1830, 1840 and 1850 сm1, –С=O(NH) at 1770 сm1, ν(C=N) at 1680 and δ(N–H) at 1640 сm1, which confirms the coordination of metals on the surface of CQDs.